Implementasi PBLTerintegrasi TaRL dan CASEL untuk Meningkatkan Peran Aktif dan Hasil Belajar Siswa pada Pembelajaran IPA - Mahardika, Nur Istiqlaliyah; Muslimah, Mar’atul; Nurita, Tutut (PendIPA Journal of Science Education, 2024)
This classroom action research aimed to improve students' activities and learning outcomes in science learning by using a problem-based learning model that includes TaRL (Teaching at the Right Level) and CASEL competencies. The subject of the research was 34 students from class VIII junior high school at SMP Negeri 1 Gresik. The results of Classroom Action research, which includes classroom observations and learning activity questionnaires, assess student learning outcomes in science learning. Research shows that students' active role increased from 55.52% to 87.61% in cycles one and two, and there was a positive correlation between active role and student learning outcomes, which increased from 23.53% to 82.34%. According to positive student feedback collected through questionnaires, this increase shows that students' active roles and learning outcomes in science learning are supported by learning activities in the problem-based learning model that integrates TaRL and CASEL. This strengthens that this approach is effective in increasing student engagement and learning outcomes in science learning.